Indirect costs of sickness absence caused by mental and behavioural disorders (ICD-10: F00-F99) in Poland in the years 2012-2018 - Bartosz Kobuszewski (Wiedza Medyczna, 2020)
Introduction: Mental health is necessary for achieving the complete health by individuals. According to WHO, it is "a state of well-being in which every individual realizes his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to her or his community" (2). Unfortunately, there is an increasing number of people suffering from mental disorders that can deteriorate their life quality, lead to problems with the standard functioning in the society, a drop in productivity, and can cause disabilities.Purpose of the article: The purpose of this article was to attempt the estimation of indirect costs of sickness absence caused by mental and behavioural disorders (ICD-10: F00-F99) in Poland in the years 2012-2018.Materials and methods: Indirect costs were estimated with the human capital approach using data on sickness absence provided by the Polish Social Insurance Institution (ZUS) and macroeconomic indicators published by the Central Statistical Office in Poland (GUS). The individual productivity loss was introduced by means of three indicators: Gross Domestic Product (GDP) per capita, Gross Domestic Product per person employed, corrected Gross Domestic Product.Results: Estimated indirect costs of sickness absence caused by mental and behavioural disorders (ICD-10: F00-F99) in Poland in 2012 were: 1.62 billion PLN measured in terms of GDP per capita, 2.86 billion PLN measured in terms of corrected GDP per person employed, and 4.40 billion PL measured in terms of GDP per person employed. And those costs in 2018 were 2.93 billion PLN, 4.57 billion PLN, and 7.03 billion PLN respectively, and they were higher by ca. 60-80% than in 2012.Conclusions: The described estimation of indirect costs can lead to conclusions that mental health care in Poland is quite poor - indirect costs can reach twice the level of National Health Fund (NFZ) expenses on the mental health care.